MEMBANGUN ECOLITERACY DI MADURA: Usulan untuk Aksi dan Proaksi - Syakur, Abd. (KARSA Journal of Social and Islamic Culture, 2012)
Abstrac Global warming is a colossal problem, that many of us considered it as a regular matter in everyday life. I believe this case is merely because we don’t know what was exactly happened. Within the scope, I try to portray the humble ‘landscape’ of Madureese community in a glance. Madureese people basically are modest, polite but may have a strong willing on things. Just like others, while facing customary problems (not beliefs, ideology, nor religion), Madureese tend to take a position apart from it. Thus, one of the significance step we should take is to raise the level of the problem up, comparable to those five principle issues (i.e., religious conviction, life, possessions, relatives, and mind). And, if it was there, we should restate it and take the proper actions and pro actions. Therefore, this small reminder may become one of my contribution to the problem, warning all of us of what we are going to face. Kata-kata kunci ecoliteracy, global warming, aksi dan proaksi